2003
DOI: 10.1002/jbm.a.10098
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐fibrous scaffolding architecture selectively enhances protein adsorption contributing to cell attachment

Abstract: Tissue engineering aims at resolving problems such as donor shortage and immune rejection faced by transplantation. Scaffolds (artificial extracellular matrices) have critical roles in tissue engineering. Recently, we developed nano-fibrous poly(L-lactic acid) scaffolds under the hypothesis that synthetic nano-fibrous scaffolding, mimicking the structure of natural collagen fibers, could create a more favorable microenvironment for cells. This is the first report that the nano-fibrous architecture built in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
447
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 647 publications
(474 citation statements)
references
References 21 publications
18
447
0
9
Order By: Relevance
“…Synthetic biodegradable polymers such as PCL, unlike natural ECM components, do not have specific cell-binding sides. Thus cell adhesion to pure synthetic polymers is poor and requires additional modifications such as adsorbing ECM proteins onto the polymer surface [48][49][50][51]. In our experiments, no additional surface modifications were necessary facilitating cell attachment onto the fibers of the hybrid scaffolds and both electrospun collagen/elastin/PCL and gelatin/PCL supported attachment and proliferation of hASCs.…”
Section: Discussionmentioning
confidence: 73%
“…Synthetic biodegradable polymers such as PCL, unlike natural ECM components, do not have specific cell-binding sides. Thus cell adhesion to pure synthetic polymers is poor and requires additional modifications such as adsorbing ECM proteins onto the polymer surface [48][49][50][51]. In our experiments, no additional surface modifications were necessary facilitating cell attachment onto the fibers of the hybrid scaffolds and both electrospun collagen/elastin/PCL and gelatin/PCL supported attachment and proliferation of hASCs.…”
Section: Discussionmentioning
confidence: 73%
“…Cells attached on nano-fibrous scaffolds at a level of 70% higher than that on solid-walled scaffolds [99]. The nano-fibrous architecture also enhanced the osteoblastic marker genes' expression ( Figure 5), indicating increased differentiation of the osteoblastic cells [100].…”
Section: Biological Effects Of Nano-fibrous Architecturementioning
confidence: 96%
“…The nano-fibrous scaffolds were found to adsorb 4.2-fold more human serum proteins than solid-walled scaffolds (control scaffolds with smooth pore wall morphology) [99]. Moreover, the profile of serum proteins adsorbed to the nanofibrous scaffold was different from that adsorbed to the solid-walled scaffolds (Figure 4).…”
Section: Biological Effects Of Nano-fibrous Architecturementioning
confidence: 97%
See 1 more Smart Citation
“…Several cells types, including osteoblasts 78,79 , fibroblasts 80,81 , rat kidney cells 80 , smooth muscle cells 82 , neural stem cells 83 and embryonic stem cells 84 , have shown increased attachment on various nano-fibers compared to their corresponding control materials. Additionally, a recent study found that branched nano-fibers improve fibroblast attachment over linear nano-fibers 85 .…”
Section: Attachment and Proliferationmentioning
confidence: 99%